TECHNOLOGICAL APPLICATIONS OF ARTIFICIAL INTELLIGENCE IN B2B MARKETING - KHRUPOVYCH, Svitlana; MAZUR, Oleksandr; SLYVIAK, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This work discusses modern applications of artificial intelligence in the field of marketing. An analysis of latest research and publications in the field of predicting consumer behavior using big data. The fact that artificial intelligence has the strongest influence and potential in development of modern tools for promotion of goods and services is argued. The optimal directions of machine data generation to provide the target audience with relevant information about the manufacturer are highlighted. Areas with the highest rate of use of artificial intelligence in business are accentuated. In this context, emphasis is placed on the creation of generated content; automated target market segmentation; conducting a competitive comparative analysis. Characteristic features that allow identifying one or other method of data processing by artificial intelligence in marketing are noted. Based on the results of the analysis, it was established that in the B2B sphere it is possible to measure and assign points to the sentiment of customers. A direction for strengthening the company’s competitive advantages through the automation of statistical methods for analyzing customer experience data is also defined. The need to study the client’s personal data in order to automate communication with them and generate content is highlighted. Recommendations for the use of artificial intelligence tools in digital advertising on various social media platforms are discussed. In this connection, the need to use neural network object recognition technologies and big data analysis of customer preferences is also explored. The possibilities of using artificial intelligence, which are the most promising in the B2B segment, have been systematized. Identified among such areas is modeling and forecasting with the help of AI-generated analytics, content generation with this technology, and business scaling through customer experience. It has been established that artificial intelligence in the B2B marketing segment provides such practical business benefits as increasing business income and profitability. It also creates an opportunity for customers to manage data for quick decision-making.